The Relatıonshıp Between Islamıc Law And Fuzzy Logıc - Yüksek, Ali; Akın, Ömer (Scientific Journal of Faculty of Theology, 2019)
We have been making frequent and evaluations in our social and scientific life. Sometimes we encounter uncertainties due to incomplete information or technical impossibilities. In these cases we need multiple logic to express events accurately. L. A. Zadeh (Lotfi Aliasker Zadeh) is the first person to put. He named it L. A. Zadeh Fuzzy Logic. In this study we will use the term “graded logic” as its Turkish equivalent. We can see similarities between Islamic law and graded logic in many respects. In fact, all acts and words of person has a value and a degree in the presence of God in Islamic law. These ratings come up with concepts such as Farz, vacip, circumcision, obscenity, mekruh, haram, etc. In this study, we will give examples of similarity relations between graduated logic and Islamic law.